The Lisson Gallery sketchbooks : Tony Fretton - Fretton, Anthony; Woodman, Ellis; Sergison, Jonathan (Drawing Matter, 2018)
Catalogue of sketches and drawings of Tony (Anthony) Fretton. When we think of the Lisson Gallery we think of the building by Tony Fretton that presents its interior to the street and builds contemporary form from the different dialects of the city around it. But that building from 1992 is in fact a continuation of the first building for the Lisson Gallery from 1986 also by Fretton, where he established ideas that were fundamental to both projects and to his practice as a whole.